Pete the cat saves up - Dean, Kim, 1969-; Dean, James, 1957- (2023)
"Pete the Cat wants a supercool Sharkbot toy, but he doesn't have enough money in his piggy bank. He takes on odd jobs -- from shoveling snow to selling lemonade and more -- and saves every penny. How long will it take for him to earn enough money to buy the toy? Early readers will love saving up with Pete!"--
Keywords: Pete, -- the Cat (Fictitious character) -- Juvenile fiction; Pete, -- the Cat (Fictitious character) -- Fiction; Pete, -- the Cat (Fictitious character); Cats -- Juvenile fiction; Toys -- Juvenile fiction; Saving and investment -- Juvenile fiction; Cats -- Fiction; Toys -- Fiction; Saving and investment -- Fiction; JUVENILE FICTION -- Animals -- Cats; JUVENILE FICTION -- Toys, Dolls & Puppets; JUVENILE FICTION -- Concepts -- Money; Saving and investment; Cats; Toys; Cats -- Juvenile fiction; Toys -- Juvenile fiction; Saving and investment -- Juvenile fiction; Cats -- Fiction; Toys -- Fiction; Saving and investment -- Fiction; Easy readers; readers; FICTION / Animals / General. -- JUV002000; Readers (Publications); Fiction; Juvenile works; Readers (Publications)